Learning and leading with habits of mind [ 16 essential characteristics for success - Costa, Arthur L.; Kallick, Bena (Gale virtual reference library, 2008)
Encompasses immediate and practical considerations that promote using the Habits of Mind in classrooms and schools every day. Also, addresses the concern for creating a learning culture that considers the Habits of Mind as central to building a thoughtful community and world